Peningkatan Pemahaman Keagamaan melalui Kegiatan Pengajian Baca Kitab di TPQ Ar Rohman Desa Candinegoro Wonoayu Sidoarjo - Adinda Oktavia (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2026)
This Community Service (PKM) activity aims to improve the religious understanding of students through reading the book at the Ar Rohman TPQ, Candinegoro Village, Wonoayu, Sidoarjo. The context of this activity is the limited skills of students in reading and understanding the contents of the book in depth, so that a more interactive and effective learning method is needed so that students are not only able to read, but also understand and practice religious values ​​in everyday life. The method used is Participatory Action Research (PAR) which involves active participation between the activity implementer, TPQ administrators, and students, with the stages of planning, implementation, observation, and reflection. The activity was carried out through reading the book together, explaining the material, as well as question and answer sessions and direct practice that were adjusted to the level of understanding of the students to be more communicative and easy to understand. The results of the activity showed that the reading the book went well and received a positive response from students, marked by an increase in reading ability and understanding of the contents of the book, activeness, enthusiasm, and courage in practice and discussion. Furthermore, this activity contributes to character development, including discipline, responsibility, patience, and self-confidence. Therefore, it is effective in enhancing religious understanding while simultaneously shaping the character of students and deserves continued development.